Escalation of antimicrobial resistance among MRSA part 2: focus on infections and treatment. Issue 2 (1st February 2023) - Lynch, Joseph P.; Zhanel, George G.
ABSTRACT: Introduction: MRSA is associated with causing a variety of infections including skin and skin structure infections, catheter and device-related (e.g. central venous catheter, prosthetic heart valve) infections, infectious endocarditis, blood stream infections, bone, and joint infections (e.g. osteomyelitis, prosthetic joint, surgical site), central nervous system infections (e.g. meningitis, brain/spinal cord abscess, ventriculitis, hydrocephalus), respiratory tract infections (e.g. hospital-acquired pneumonia, ventilator-associated pneumonia), urinary tract infections, and gastrointestinal infections. The emergence and spread of multidrug resistant (MDR) MRSA clones has limited therapeutic options. Older agents such as vancomycin, linezolid and daptomycin and a variety of newer MRSA antimicrobials and combination therapy are available to treat serious MRSA infections. Areas covered: The authors discuss infections caused by MRSA as well as common older and newer antimicrobials and combination therapy for MRSA infections. A literature search of MRSA was performed via PubMed (up to September 2022), using the keywords: antimicrobial resistance; β-lactams; multidrug resistance, Staphylococcus aureus, vancomycin; glycolipopeptides. Expert opinion: Innovation, discovery, and development of new and novel classes of antimicrobial agents are critical to expand effective therapeutic options. The authors encourage the judicious use of antimicrobials in accordance with antimicrobial stewardship programs along with infection-control measures to minimize the spread of MRSA.